Status Gizi, Riwayat Penyakit Tidak Menular Dan Kebiasaan Olahraga Pada Lansia Di Posyandu Lansia Kelurahan Kotabumi Tengah Kabupaten Lampung Utara - Novaliano Alfariji Ramadhan; Sutrio Sutrio (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Nutritional problems that are often experienced by the elderly in addition to malnutrition, obesity problems are also often experienced by the elderly, which can arise because activity in this group has decreased while food intake is not reduced or even excessive, The purpose of the study was to determine the description of nutritional status and history of non-communicable diseases and exercise habits in the elderly at the Elderly Posyandu, Kotabumi Tengah Village, North Lampung Regency. The type of research used was descriptive research with a cross-sectional approach. The location of the study was at the Elderly Posyandu, Kota Bumi Tengah Village with a population of 48 people. The variables used were nutritional status, disease history, exercise habits and characteristics (gender, age, education, work). The data collection method used was Random Sampling (simple random). Data collection in this study used a questionnaire in the form of questions to determine the nutritional status, disease history and exercise habits of elderly participants. Data analysis used univariate analysis. The results of the study obtained as many as the nutritional status of the elderly according to BMI, namely 5% very thin, 5% thin, 57.5% normal, 15% fat, 17.5% obesity, history of NCDs in the elderly category who have a history of NCDs 85%, those who do not have a history of NCDs 15%, exercise habits in the elderly category rarely / do not exercise 62.5%, often exercise 37.5%. It is hoped that health workers can increase the knowledge of the elderly about non-communicable diseases by providing education and assistance. Counseling is more interactive, creative with lecture methods and two-way discussions with adult learning methods.